Engineering mathematics - Gangadharan, A. (New Age International, 2001)
This book is the outcome of author teaching experience in Mathematics, for over 33 years. Basic concepts and fundamentals are explained in a lucid manner. A number of worked out examples have been given, and sufficient number of problems are included in the exercises (Problems for Practice). Another distinguishing feature of this book is that short answer questions are listed, and "things to remember" a given.